Test and simulation on moisture flow in earlyage concrete under drying. Issue 2 (25th January 2018) - Zhang, Jun; Wang, Jiahe; Ding, Xiaoping
ABSTRACT: In this paper, moisture flow in two concrete with and without internal curing using presoaked lightweight aggregate (PSLWA) under surface drying is experimentally investigated by measuring the weight of the concrete samples. Mathematical modeling on moisture flow, especially moisture transfer coefficient between concrete and surrounding air, normally called surface factor is performed. The results show that moisture flow through the drying surface of concrete can be characterized by a constant moisture loss stage (I) followed by a gradually reducing moisture loss stage (II). For the given environmental condition, the length of stage I increases with a decrease in water-to-cement ratio. Internal curing with PSLWA will prolong the length of Stage I. Surface factor is a function of location along air flow direction, air flow speed, and temperature of air and concrete surface, while it is independent of mix proportions of concrete. Higher air flow rate, higher temperature of air and/or concrete will result in a larger surface factor. Element size along air flow direction significantly influences the value of surface factor. Smaller element size along the air flow direction will result in a larger surface factor. The comparison on surface factor between experimental determination and theoretical calculation is performed and a good agreement between them is obtained.